2021
DOI: 10.3390/foods10122960
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Lactic Acid Bacteria with In Vitro Probiotic-Related Characteristics from the Cactus Pilosocereus gounellei (A. Weber ex. K. Schum.) Bly. ex Rowl

Abstract: Pilosocereus gounellei (A. Weber ex. K. Schum.) Bly. ex Rowl., popularly known as xique-xique, is a cactus from the Caatinga biome, which is rich in bioactive compounds but has not been previously studied as a source of lactic acid bacteria (LAB) with probiotic aptitudes. This study aimed to identify, characterize, and select LAB isolates with in vitro probiotic-related characteristics from xique-xique cladodes and fruit. Isolates with the most promising probiotic-related characteristics were evaluated regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Other researchers have used a similar multivariate approach to identify putative probiotics from different sources that may be complementary or antagonistic depending on the physiological performance of species and strains. Sampaio et al (2021) selected four LAB strains identified as L. paracasei and L. casei using PCA that showed the consistent results in terms of antagonistic activity, autoaggregation, acid and bile salt tolerance, co-aggregation, and hydrophobicity. In addition, Vijayalakshmi et al (2020) combined PCA with other statistics such as heat map and network analyses to determine the most promising LAB strains (L. casei, L. plantarum, and L. rhamnosus) with different bioactivities similar to the previous report.…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers have used a similar multivariate approach to identify putative probiotics from different sources that may be complementary or antagonistic depending on the physiological performance of species and strains. Sampaio et al (2021) selected four LAB strains identified as L. paracasei and L. casei using PCA that showed the consistent results in terms of antagonistic activity, autoaggregation, acid and bile salt tolerance, co-aggregation, and hydrophobicity. In addition, Vijayalakshmi et al (2020) combined PCA with other statistics such as heat map and network analyses to determine the most promising LAB strains (L. casei, L. plantarum, and L. rhamnosus) with different bioactivities similar to the previous report.…”
Section: Resultsmentioning
confidence: 99%
“…Sci. 2023, 13, 12780 2 of 18 that strains considered probiotics can be extracted from fermented products of animal origin [7][8][9] and plant origin [10][11][12][13]. Traditional fermented products are a rich source of microorganisms, some of which may have probiotic properties [14].…”
Section: Introductionmentioning
confidence: 99%